Total quality management - Camilar-Serrano, Angelita Ong (Manila: Unlimited Books Library Services & Publishing Inc., 2016)
Chapter I: Introduction to TQM --Chapter 2: Strategic dimensions of quality --Chapter 3: Gurus of TQM --Chapter 4: Kaizen: Concepts and systems --Chapter 5: Good Housekeeping --Chapter 6: Phrases in TQM implementation --Chapter 7: TQM and planning tools --Chapter 8: Customer value strategy --Chapter 9: Quality standards.
Chapter 1. -- Introduction to TQM -- 2. Strategic dimensions of quality -- 3. Gurus of TQM -- 4. Kaizen : concepts and systems -- 5. Good housekeeping -- 6. Phases in TQM implementation -- 7. TQM and planning tools -- 8. Customer value strategy -- 9. Quality standards.
Includes bibliography.
Keywords: Management